Substrate Preference Pattern of Agaricus meleagris Pyranose Dehydrogenase Evaluated through Bioelectrochemical Flow Injection Amperometry. Issue 3 (23rd October 2018) - Rafighi, Parvin; Bollella, Paolo; Pankratova, Galina; Peterbauer, Clemens K.; Conghaile, Peter Ó; Leech, Dónal; Haghighi, Behzad; Gorton, Lo
Abstract: Pyranose dehydrogenase (PDH) is a quinone‐dependent extracellular flavoglycoprotein mainly produced by litter‐decomposing fungi and contributes to the degradation of lignocellulose. PDH in terms of structure and catalytic features pertains to the glucose methanol‐choline oxidoreductase family and oxidizes a wide substrate range of aldopyranoses including hexoses, pentoses, disaccharides and oligosaccharides with a high degree of regioselectivity. The purpose of this study was to rationalize the preference of PDH immobilized on an electrode with the structural features of various substrates and thus the kinetic constants were measured for various sugars. PDH was co‐immobilized on the electrode with an osmium redox polymer. Response currents for different sugars were measured using flow injection amperometry at +0.3 V vs. Ag|AgCl, KCl (0.1 M). The Michaelis‐Menten constants, the turnover numbers and the catalytic efficiency were calculated and revealed that type, orientation and configuration of the substituent play a major role on substrate preference. An OH‐group at C‐1 and C‐6 are not essential and substrate specificities are little affected by the substitution at C‐1. The presence and orientation of OH− at C‐2 and C‐3 are relevant for reactivity. Orientation of OH− at the C‐4 position has little effect, and sugars with a substitution below the plane at C‐5 are not suitable as substrate. Highest activity for oxidation of glucose, mannose and sucrose was detected at pH 8.5. Abstract : Substrate Preference Pattern : the kinetic constants are used to rationalize the preference of Am PDH with the structural features of various substrates. All substrates have a hydroxyl group below and above the plane of the ring at C‐2 and C‐3, respectively and there is a preference for a hydroxyl group at C‐4 without a certain superiority in orientation. Sugars with substitutions below the plane of the ring at C‐5 do not show activity and a free hydroxyl group at C‐1 and C‐6 is not required.